Comparison of Cytologic Characteristics between Adenoid Cystic Carcinoma and Adenoid Basal Carcinoma in the Uterine Cervix - Juhyeon Jeong; Seung Yeon Ha; Hyun Yee Cho; Dong Hae Chung; Jungsuk An (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Adenoid cystic carcinoma (ACC) and adenoid basal carcinoma (ABC) are rare in the uterine cervix. ACC is more aggressive than ABC, thus accurate differential diagnosis is important. In this study, we identified cytologic features useful in distinguishing these two tumors for diagnosis. Methods: Three cases of ACC and five cases of ABC were selected for this study. Cervicovaginal smear slides were reviewed retrospectively, and the area, circumference, major axis, and minor axis of nuclei were measured using an image analyzer. Results: ACC displayed three-dimensional clusters with a small acini pattern. ABC displayed peripheral palisading without an acini pattern. The nuclei of ACC were more irregular and angulated than those of ABC, and the former showed a coarsely granular chromatin pattern. The nucleic area, circumference, major axis, and minor axis were 18.556±8.665 µm2, 23.320±11.412 µm, 5.664±1.537 µm, and 4.127±1.107 µm in ACC and 11.017±4.440 µm2, 15.920±5.664 µm, 4.612±1.025 µm, and 3.088±0.762 µm in the cases of ABC. All measured values showed statistically significant difference (p < .001). Conclusions: Although the nuclei of both of these tumor types were oval shaped, inferred from the ratio of minor axis to major axis (0.728 in ACC and 0.669 in ABC), the area of nuclei was approximately 1.7 times larger in ACC than in ABC. Distinguishing nucleic features, including area, morphology, and chromatin pattern, may be helpful in making a correct diagnosis.